The colonic groove of the plains viscacha (Lagostomus maximus) : Histochemical evidence of an abrupt change in the glycosylation pattern of goblet cells - Tano de la Hoz, María Florencia (2017)
The ascending colon of most rodent species shows a longitudinal colonic groove that works as a retrograde transport pathway for a mixture of bacteria and mucus toward the cecum. We describe the morphology and glycosylation pattern of the colonic groove of Lagostomus maximus to analyze the role of mucins in this anatomical feature. We also studied the distribution pattern of the interstitial cells of Cajal (ICC) to evaluate their regulatory influence on gut motility. The groove originated near the cecocolic junction and extended along the mesenteric side of the ascending colon, limited at both ends by nonpapillated ridges. These ridges divided the lumen of the ascending colon into two compartments: a narrow channel and a large channel, called the groove lumen and the main lumen, respectively. The histochemical analysis showed differences in the glycosylation pattern of the goblet cells inside and outside the groove. Unlike the mucosa lining the main lumen of the colon, the groove was rich in goblet cells that secrete sulfomucins. The PA/Bh/KOH/ PAS technique evidenced an abrupt change in the histochemical profile of goblet cells, which presented a negative reaction in the groove and a strongly positive one in the rest of the colonic mucosa. The anti-c-kit immunohistochemical analysis showed different ICC subpopulations in the ascending colon of L. maximus. Of all types identified, the ICC-SM were the only cells located solely within the colonic groove.